2013
DOI: 10.1099/ijs.0.043844-0
|View full text |Cite
|
Sign up to set email alerts
|

Sphingobacterium psychroaquaticum sp. nov., a psychrophilic bacterium isolated from Lake Michigan water

Abstract: A psychrophilic, Gram-negative bacterium, designated MOL-1 T , was isolated from water of Lake . The major cellular fatty acids were iso-C 15 : 0 , iso-C 17 : 0 3-OH and summed feature 3 (iso-C 15 : 0 2-OH and/or C 16 : 1 v7c). Menaquinone MK-7 is the predominant respiratory quinone, while symhomospermidine is the predominant polyamine. The polar lipid profile is composed of the predominant lipids phosphatidylethanolamine and unidentified polar lipid L2, with moderate amounts of unidentified polar lipids L1, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…The quinone system consisted of menaquinone MK-7 (99 %) and MK-6 (1 %). Both polyamine pattern (Hamana & Matsuzaki, 1991;Albert et al, 2013) and quinone system were in accordance with the characteristics of other species of the genus Sphingobacterium. In the polar lipid profile (Fig.…”
supporting
confidence: 50%
“…The quinone system consisted of menaquinone MK-7 (99 %) and MK-6 (1 %). Both polyamine pattern (Hamana & Matsuzaki, 1991;Albert et al, 2013) and quinone system were in accordance with the characteristics of other species of the genus Sphingobacterium. In the polar lipid profile (Fig.…”
supporting
confidence: 50%
“…The low-temperature habitat represents hot spots of biodiversity, and several novel cold-adapted microbial species have been sort out from cold environments including Cellulophaga algicola [40], Cryobacterium roopkundense [41], Exiguobacterium soli [42], Flavobacterium frigidarium [43], Flavobacterium psychrolimnae [44], Glaciimonas frigoris [45], Hymenobacter roseosalivarius [46], Lacinutrix jangbogonensis [47], Massilia eurypsychrophila [48], Octadecabacter arcticus [49], Oleispira antarctica [50], Pedobacter arcticus [51], Pseudomonas extremaustralis [52], Psychrobacter pocilloporae [53], Psychromonas ingrahamii [54], Sphingobacterium psychroaquaticum [55], and Sphingomonas glacialis [56]. Along with novel species of psychrotrophic microbes, some microbial species such as Arthrobacter nicotianae, Brevundimonas terrae, Paenibacillus tylopili, and Pseudomonas cedrina have been isolated and characterized for multifarious PGP attributes at low temperatures from cold deserts of NW Himalayas [7].…”
Section: Biodiversity Of Beneficial Microbiomesmentioning
confidence: 99%
“…They reported that Betaproteobacteria predominated, followed by Bacteroidetes and Alphaproteobacteria. There are however, no published reports that characterized the microbial community in Lake Michigan potable water, although Albert et al (2010Albert et al ( , 2013Albert et al ( , 2014 have reported the isolation of several novel bacterial species and a novel genus of bacteria from Lake Michigan potable water.…”
mentioning
confidence: 99%
“…If turbidity was observed, tubes were streaked to PCA to determine the identity of the bacterium present. Aerobic acid production from sugars was performed using the method described in Albert et al (2013) with incubation at 25 C for up to 14 days. Production of cell-bound orange pigments was determined by the technique of Yabuuchi et al (1983).…”
mentioning
confidence: 99%